ANALYSIS BUDGET REALIZATION, PROSPECTIVE PROVIDER FOR THE FUTURE PROJECTS AT PT SERINDO - Muhammad Nur Rizqi (The Accounting Journal of Binaniaga, 2016)
Facing huge economic development and competition, a construction service company should have to be aware of it by implementing a good management to provide a good planning especially how to execute the future projects properly by re-evaluating the previous projects had been done. The objective of this research is to find out that the provider and the type of the project have influenced the realization of the company’s budget. And to study whether the budget realization is a variable to measure the success of a project. The writer has applied a quantitative data refers to budget and budget realization. He has been using SPSS program version 11.5 to obtain the regression approach and distinctive test to evaluate the project conducted by the company. He has been applying a discriminatory measures to evaluate the provider which is providing a high profit to the company. Result of this research has declared that either SNS and Protelindo provider dealing with various projects of SITAC and CME has been influencing the budget realization of the company, and budget realization is considered as a predictor variable against the success of each project. Keywords: budget realization, prospective provider for the future projects.